ANALISIS STRATEGI BISNIS DAN DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN PADA UMKM KEBULI ABUYA - Ahmad Munadhir Amri (Develop: Jurnal Ekonomi Pembangunan, 2022)
This study aims to find out: 1) digital marketing applied by Kebuli Abuya, 2) the role of digital marketing in increasing sales of Kebuli Abuya, and; 3) identifying strengths, weaknesses, opportunities, and threats available using SWOT, STP, Marketing Mix Analysis. The method used in this study is qualitative-descriptive research. Data collection is done by interview, observation, and documentation. The results of the study were based on the SWOT analysis, the researchers then conducted an Internal Strategic Factors Analysis Summary (IFAS) analysis which showed that the internal aspects of the highest score were in service, food menu, and brand image. Meanwhile, based on the External Strategic Factors Analysis Summary (EFAS) analysis, it shows that the growth of Kebuli Abuya is largely determined by the customers, and how loyal customers are able to provide increased sales for Kebuli Abuya. Strategy side of practices digital marketing, Kedai Abuya through social media such as Instagram, Facebook, LinkedIn, and another internet network that are connected to the reach of consumers (online food delivery)such as Go-food, Grab food, and Traveloka eat. The application of digital marketing by Kedai Abuya has an effect of 30% - 40% in helping the sale.